HUBUNGAN ANTARA KECERDASAN INTRAPERSONAL DENGAN KECERDASAN EMOSIONAL - Cut Maitrianti (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
Intrapersonal intelligence is a part of emotional intelligence because emotional intelligence has two abilities: intrapersonal skills and interpersonal skills. Therefore, emotional intelligence, it has five elements that are composite rather than intrapersonal intelligence and interpersonal intelligence. Five elements are self-awareness, self-settings, motivation, empathy, and social. The first three elements are part of intrapersonal intelligence, self-awareness, self-settings, and motivation, while the latter two are part of interpersonal intelligence, empathy, and social. Intelligence here is shrewdness and skill.